2004
DOI: 10.1186/1471-2407-4-23
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach in the treatment of neuroendocrine gastrointestinal tumors: Additive antiproliferative effects of interferon-γ and meta-iodobenzylguanidine

Abstract: Background: Therapeutic options to effectively inhibit growth and spread of neuroendocrine gastrointestinal tumors are still limited. As both meta-iodobenzylguanidine (MIBG) and interferon-γ (IFNγ) cause antineoplastic effects in neuroendocrine gastrointestinal tumor cells, we investigated the antiproliferative effects of the combination of IFNγ and non-radiolabeled MIBG in neuroendocrine gut STC-1 and pancreatic carcinoid BON tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…These observations suggest that infection and inflammation of the GI tract cause significant alteration in enterochromaffin cell function and 5-HT production and the immunological profile of the inflammatory response may be an important determinant of the changes that occur in the 5-HT response in the gut. Our findings on Th1/Th2 regulation of enterochromaffin cell biology corroborate with recent studies on lower numbers of enterochromaffin cells and a lower amount of 5-HT in Th1-biased bacterial infection with C rodentium 31 and on the inhibitory effect of IFN-γ on the proliferation of BON tumour cells (model of human enterochromaffin cells) 32. Related to this it has recently been shown that the rate of epithelial cell turnover in the large intestine was higher in resistant BALB/c mice in T muris infection compared with that in susceptible AKR mice and that the rate of epithelial cell movement is under immune control by IL13 33.…”
Section: Discussionsupporting
confidence: 91%
“…These observations suggest that infection and inflammation of the GI tract cause significant alteration in enterochromaffin cell function and 5-HT production and the immunological profile of the inflammatory response may be an important determinant of the changes that occur in the 5-HT response in the gut. Our findings on Th1/Th2 regulation of enterochromaffin cell biology corroborate with recent studies on lower numbers of enterochromaffin cells and a lower amount of 5-HT in Th1-biased bacterial infection with C rodentium 31 and on the inhibitory effect of IFN-γ on the proliferation of BON tumour cells (model of human enterochromaffin cells) 32. Related to this it has recently been shown that the rate of epithelial cell turnover in the large intestine was higher in resistant BALB/c mice in T muris infection compared with that in susceptible AKR mice and that the rate of epithelial cell movement is under immune control by IL13 33.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, in vitro studies using BON tumour cells (model of human EC cells) have shown that interferon c exerts antiproliferative effects on these cells and inhibits 5-HT production from these cells. 42 Our present results provide clear evidence of CD4 + T cell-mediated immunological control of EC cell hyperplasia and 5-HT production in intestinal infection and CD4 + T cells in 5-HT production inflammation. The transfer of purified CD4 + T cells from infected mice into naive SCID mice significantly increased the number of EC cells and the amount of 5-HT.…”
Section: Discussionsupporting
confidence: 64%
“…Western blotting was performed as described previously [30] . In brief, whole-cell extracts were prepared by lysing cells.…”
Section: Western Blot Analysismentioning
confidence: 99%